2021
DOI: 10.1371/journal.pone.0241882
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorods enhance different immune cells and allow for efficient targeting of CD4+ Foxp3+ Tregulatory cells

Abstract: Gold nanoparticles (AuNPs) hold great promise in nanomedicine, yet their successful clinical translation has not been realized. Some challenges include effective AuNP targeting and delivery to improve modulation of immune cells of interest while limiting potential adverse effects. In order to overcome these challenges, we must fully understand how AuNPs impact different immune cell subsets, particularly within the dendritic cell and T cell compartments. Herein, we show that polyethylene glycol coated (PEG) gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Gold nanoparticles, such as 20 nm citrate-covered gold nanoparticles (cit-AuNP), have been demonstrated to have important antiinflammatory properties in the brain of sepsis and are promising as adjunctive agents in sepsis treatment with antibiotics to avoid SAE (111). Hyperforin-loaded gold nanoparticles, gold nanorods/compounds and anti-inflammatory nanoparticles have the ability to improve symptoms by inhibiting the differentiation of Th1 and Th17, while promoting the accumulation of T regs and Th2 in the treatment of EAE, cancer, and muscular dystrophy (112)(113)(114). Therefore, gold nanoparticles can have therapeutic interest to promote T regs accumulation in the context of SAE.…”
Section: Inducing the Accumulation Of T Regs In The Brainmentioning
confidence: 99%
“…Gold nanoparticles, such as 20 nm citrate-covered gold nanoparticles (cit-AuNP), have been demonstrated to have important antiinflammatory properties in the brain of sepsis and are promising as adjunctive agents in sepsis treatment with antibiotics to avoid SAE (111). Hyperforin-loaded gold nanoparticles, gold nanorods/compounds and anti-inflammatory nanoparticles have the ability to improve symptoms by inhibiting the differentiation of Th1 and Th17, while promoting the accumulation of T regs and Th2 in the treatment of EAE, cancer, and muscular dystrophy (112)(113)(114). Therefore, gold nanoparticles can have therapeutic interest to promote T regs accumulation in the context of SAE.…”
Section: Inducing the Accumulation Of T Regs In The Brainmentioning
confidence: 99%
“…It was demonstrated that when C57BL/6 splenocytes were treated with polyethylene‐glycol‐coated gold nanorods (PEG–AuNRs) and PEG–AuNRs covered with a thin layer of silver, only PEG–AuNRs could enhance cluster of differentiation (CD)4+ Foxp3+ regulatory T cells response. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Moreover, AuNPs of diverse size and shape have been shown to induce expression of distinct inflammatory cytokines in bone-marrowderived dendritic cells (BMDCs). [13,14] Different surface chemistries of AuNPs have also been shown to affect inflammatory processes, as measured by downregulated interleukin (IL)-1𝛽 levels, both in vivo and in vitro using a human monocyte cell line. [15] Furthermore, the surface composition of AuNPs affects activation and function of different dendritic cells (DCs) and T cell subsets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation